The Pollution Status of Some Selected Rivers in Ado-Ekiti, Nigeria (Biological Sciences - PJSIR, 2007)
The poll uti on statu s of th ree r i vers (Ureje, Awcda l e and Ologan ) i n Ado-Eki t i , Eki t i State, N i geri a was i n vesti gated by carryi ng out necessary physicoch emical , microbiol ogical and heavy m etal (elementa l ) an a l yses on th em. Twenty physicochemical parameter s were determi ned, notable resu l ts were as fol lows; Temperature ran ged from 25 .01 -26.0 I °C; Colour, 29.30 - 35.16 true colour unit s (TCU), pH 6. 1 5 - 6.58; total suspend ed solids (TSS), 0. I O - 1 .00 mg/ I ; total di s solved  sol ids (TDS), 1 00 - 284 m g/I ; total  sol ids (TS), 1 56 - 394 mg/I ; acid i t y,  1.08 -  1.32 m g/ I    CaCO,; tota l     h ardness, I 00.2 - I 06.8 mg/ I CaC03 ; chloride, 0.61 - 0.71 mg/l ; ni t rate, 2.00 - 7.55 mg/ I ; sul ph ate, 2.50 - 3. 1 6 mg/ I ; dissolved oxygen (DO), 5.80 - 7.10 mg/I ; biochemical oxygen demand (BOD), 1 2.5 - 1 1 1 .85 mg/ I and chemical oxygen demand (COD), 1 7.70-  1 83. 1 2 mg/ I. R iver Ol ogan sh owed hi ghest val ues for col our, turbi di ty  a l kal i n i ty as H   o;, n i trate, chlorid e, BOD andCOD. For r iver U reje, tem peratu re, pH , cond uctiv ity, TDS, TS and total al kal i nity were the h i gh est. R i ver Awedal e was high i n tota l  h ardness and sulphate . The elementa l  an al yses a l so revealed t h at Cu, Cr, Pb, Mn and Cd were si gn i fica n tly hi gh i n ri ver Ologan . Pb, Cr an d Cd were non detected i n Urcj c wh i le Cr an d Cd were a l so non detected i n Aweda l e. Majori ty of th e resu lts obtained for th e physi coch emical an d e l emental analyses fa r exceed ed th e WHO recom m ended va l ues. Si mi l a r l y the bacteriological anal ysis i ndicated the presence of col i form bacteri a i n al l the ri vers above the WHO recommend ed va l u es. I t can be concl uded that all the ri vers are h eav i l y poll uted wi th  the degree of poll ution bei n g Ologan > Aweda l e > Ureje.